Emotions in groups, organizations and cultures - Ashkanasy, Neal M. 1945-; Härtel, Charmine E. J. 1959-; Zerbe, W. J. (Emerald, 2009)
The study of emotions in organizations is unlocking new and exciting insights into why employees behave as they do in groups, organizations and in different cultural contexts. In this 5th volume of Research on Emotion in Organizations, a collection of the latest work advancing knowledge and practice in these areas is showcased. The readings will appeal to all seeking a better understanding of the social and emotional competencies that help employees thrive in the workplace, the types of emotional self-management strategies employees use in managing emotion work and how the work context affects these, the impact of emotional displays in the workplace on performance appraisal and perceived organizational commitment, the role of unconscious affect on attitudes and behaviors at work, how interpersonal relationships between co-workers affect vitality and job performance, cross-national and cross-cultural issues, and how to build positive work environments.